National study of physical and sexual assault among women with disabilities. Issue 2 (3rd April 2008) - Casteel, C; Martin, S L; Smith, J B; Gurka, K K; Kupper, L L
Abstract : Objective: To examine the association between the level of disability impairment and physical and sexual assault in a sample of US women at least 18 years of age. Design, setting and participants: Retrospective longitudinal study of 6273 non-institutionalized US women from 8000 women participating in the 1995–1996 National Violence Against Women (NVAW) Survey. Main outcome measure: Women's experiences of physical and sexual assault in the 12 months before the NVAW interview. Results: Most women reported having no disability (n = 5008, 79.8%) and/or not experiencing an assault in the year before their interview (n = 6018, 95.9%). Less than 5% (n = 280) reported having a disability that severely limited daily activities, and 15.7% (n = 985) reported having a disability that moderately limited activities. Less than 4% (n = 218) of the women reported a physical-only assault, and less than 1% (n = 37) reported being sexually assaulted. Women with severe disability impairments were four times more likely to be sexually assaulted than women with no reported disabilities (RR = 4.0, 95% CI 1.5 to 10.6). Little difference in the risk of sexual assault was found between women with moderate disability impairments and those reporting no disabilities (RR = 1.0, 95% CI 0.3 to 2.8). Women with severe (RR = 1.6, 95% CI 0.9 to 3.0) and moderate (RR = 1.2, 95% CI 0.8 to 1.9) disability impairments were at greater risk, although not quite significantly so, of physical-only assault than were women without a disability. Conclusion: The findings suggest that women with disabilities that severely limit activities of daily living are at increased risk of sexual assault.